Numerical Investigation of Bottom Step Height Effect on The Hydrodynamic Performance of High-Speed Planing Crafts - Mo'men Gaafary; Muhammad Fahmy; Mostafa Mohammed Mostafa (Port Said Engineering Research Journal, 2023)
The utilization of transverse steps at the bottom of high-speed planning crafts, represents an important geometric modification to improve their hydrodynamic performance. However, there are insufficient research investigations on the hydrodynamic effects of various step geometries on the performance of these stepped crafts. This paper aims to address this research gap by examining different types of steps and their potential impact on the hydrodynamic performance of stepped crafts. Ansys-Fluent, as a CFD software, is applied in this article, to investigate the performance of stepped planing crafts. The results are validated using both experimental and numerical data. For this study, three different step heights are considered, and a standard k–ε turbulence model is chosen. The distribution of pressure on the hull and the lift/drag ratios of high-speed stepped planing craft are determined, Additionally, a multiphase Volume of Fluid (VOF) model is employed for simulating the free-surface flow over the hull and calculations are performed over a specified speed range for each step height. The results demonstrate that the step height positively affects the hydrodynamic performance of the investigated crafts. The most appropriate step height is identified and recommended for optimal performance.